(untitled) (Agro Productividad, 2023)
Objective: To evaluate the diversity and abundance of rodent species, as well as vegetation cover, under three habitat conditions in the Altiplano Potosino Oeste. Design/Methodology/Approach: The work was carried out in eight sites with good (3), regular (2), and poor (3) vegetation cover conditions. Frequency, basal, and aerial cover data were collected in three plot sizes to obtain the results for the three types of vegetation: arborescent stratum (20×20 m), shrubs (3 plots of 5×5 m), and herbaceous stratum (2 plots of 1×1m). In order to collect the rodent data, three sampling nets with 100 Sherman traps were used. Rodent species diversity was determined using the Shannon-Whinner index (SWI), while abundance was obtained using the Relative Density Index (RDI). Differences were determined using ANOVA. Results: Grass cover decreased depending on the condition; however, this was not the case of the shrub cover. The overall diversity of rodent species was 21 (16 in fair, 15 in good, and 14 in poor condition). The total SWI and RDI decreased depending on the condition. Dipodomys ornatus, D. merriami, and Chaetodipus nelsoni were the most abundant and most widespread species. Study Limitations/Implications: The study was conducted during the most restrictive season and under drought conditions. This situation impacted cattle, but not rodents. However, although their plasticity maintained relatively stable RDI values, the indices decreased depending on the condition. Findings/Conclusions: Despite their habitat conditions, the rodents found in the area are more diverse and abundant than those reported in reference works. Therefore, further studies about this subject should be carried out using rodents as bioindicators